Description of a new species of Plutomurus Yosii (Collembola: Tomoceridae) from Georgia, Caucasus and notes on the morphology of Plutomurus birsteini Djanashvili & Barjadze - Barjadze, Shalva; Giordano, Rosanna; Soto-Adames, Felipe (Zootaxa, 2020)
Plutomurus jordanai sp. nov. from Zeda Kvilishori Cave (Tskaltubo Municipality, Imereti region, Western Georgia) is described, illustrated and differentiated from other morphologically similar species‒‒P. kelasuricus Martynova, 1969 and P. eristoi Barjadze, Baquero, Soto-Adames, Giordano & Jordana, 2016. In addition, morphological characters omitted or erroneously provided in the original description of Plutomurus birsteini Djanashvili & Barjadze, 2011 are described and illustrated from the specimen sampled in the type locality‒‒Sakishore Cave (Racha region, Western Georgia). An identification key to the species of the genus Plutomurus reported from the Caucasus is presented. A list of the invertebrate communities for Zeda Kvilishori and Sakishore caves is provided.